Effect of Public Elementary School Financial Challenges on Student Achievement - Wibowo, Syahriar Ardanto; Rukayah, Rukayah (Jurnal Ilmu Pendidikan, 2019)
The quality of education is often seen from the achievements of students. Meanwhile, student achievement in school is influenced by many factors. The financing factor is one factor that cannot be separated from the teaching and learning process. The relationship between educational funding and student achievement is still being debated. This study aims to reveal the relationship between the number of funding resources in schools and student achievement. This research used qualitative methods. Data collection was carried out using interviews, observation, and documentation techniques. The collected data were analyzed using interactive model analysis and purposive sampling techniques. The results of this study indicate that public elementary schools have limited sources of funding. The amount of money managed by one school differs depending on the number of students and the ability of parents. This study finds that education funding has no direct effect on student achievement. Schools that have significant financial resources do not necessarily have high achievements. The effectiveness of schools in managing their finances also becomes essential. Besides, the role of policymakers, the ability of teachers, and the participation of parents are crucial to increase the education quality.